Media as watchdogs: The role of news media in electoral competition - Jimmy Chan; Wing Suen (The Johns Hopkins University, Department of Economics, 2003)
We present a model in which the media provide voters with information that is tainted by their own preferences, and derive an equilibrium in which media endorsements influence voting behavior. Competition for media endorsement causes political parties to adopt more centrist policies, which benefits all voters. Mass media which are more sensitive to changes in policies and which are less biased lead to greater policy convergence toward the median voter's ideal point. The presence of multiple media outlets also helps promote electoral competition.
Keywords: D72; D82; 330; media bias; cheap talk; policy convergence; Kommunikationsmedien; Wahlverhalten; Wettbewerb; Theorie; Wahlkampf